Lymphocyte Transformation Testing (LTT) in Cases of Pain Following Total Knee Arthroplasty: Little Relationship to Histopathologic Findings and Revision Outcomes. (6th February 2019) - Yang, Steven; Dipane, Matthew; Lu, Conrad H.; Schmalzried, Thomas P.; McPherson, Edward J.
Abstract : Background: The utilization of lymphocyte transformation testing (LTT) has increased for diagnosing metal sensitivity associated with total knee arthroplasty (TKA), but its validity for the diagnosis of TKA failure due to an immune reaction has not been established. In this study, we sought to characterize the relationship of a positive LTT result to histopathologic findings and clinical and functional outcomes. Methods: This was a retrospective study of 27 well-fixed, aseptic, primary TKA cases in which the patient had persistent pain and/or stiffness and underwent revision due to a suspected metal allergy to nickel, as determined on the basis of positive LTT. Revision procedures were performed by a single experienced arthroplasty surgeon. Periprosthetic tissue samples obtained at the time of revision surgery were scored using the aseptic lymphocyte-dominated vasculitis-associated lesion (ALVAL) scoring system. Results: Eight patients were categorized as mildly reactive; 8 patients, moderately reactive; and 11 patients, highly reactive to nickel by LTT. The predominant findings on routine histopathologic analysis were fibrosis and varying degrees of lymphocytic infiltration in 17 (63%) of the 27 cases. The average ALVAL score of the cohort was 3.1 ± 1.9, of a maximum score of 10. Average Knee Society Score (KSS) values improved post-revision, as did range of motion (all p < 0.01). Neither LTT stimulation index as a continuous variable nor as a categorical variable (mildly reactive, moderately reactive, highly reactive) was correlated with ALVAL score, pre-revision function (as assessed by KSS-clinical, KSS-functional, and range of motion), or change in function at the most recent follow-up (0.015 < r < 0.30, 0.13 < p < 0.95). In addition, the ALVAL score did not correlate significantly with either pre-revision or post-revision KSS or range of motion (0.061 < r < 0.365, 0.09 < p < 0.88). Conclusions: On the basis of this analysis, including histopathologic assessment, LTT results alone were insufficient for the diagnosis of TKA failure due to an immune reaction. A positive LTT may not indicate that an immune reaction is the cause of pain and stiffness post-TKA. The role of LTT in assessing TKA failure from an immune reaction needs further investigation. Diagnostic criteria for such TKA failure need to be established. Level of Evidence: DiagnosticLevel IV . See Instructions for Authors for a complete description of levels of evidence.